2018
DOI: 10.12691/education-6-11-18
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Student Worksheet Based on PISA to Improve Problem Solving Ability

Abstract: Problem solving ability is an ability that sudent have to achieve after learning mathematics. This ability can be trained through using appropriate problems on student worksheets. The purpose of this study was to produce effective worksheet based on PISA and be able to improve students' problem solving abilities. The type of research is the research development that use Dick & Carey models. The trials in this study were carried out in the X IA 3 and X IA 5 classes of Brigjend Katamso I Medan. From the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…This means that students were helped by implementing teaching materials to carry out analysis and evaluation activities in Impulse and Momentum subjects. Some have shown that teaching materials are useful in terms of student responses, which is supported by research [28] on students' positive responses to learning using teaching materials. The same thing was expressed by [7], [37] that the teaching materials developed were useful in terms of validity, practicality, and increased understanding of concepts.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This means that students were helped by implementing teaching materials to carry out analysis and evaluation activities in Impulse and Momentum subjects. Some have shown that teaching materials are useful in terms of student responses, which is supported by research [28] on students' positive responses to learning using teaching materials. The same thing was expressed by [7], [37] that the teaching materials developed were useful in terms of validity, practicality, and increased understanding of concepts.…”
Section: Discussionmentioning
confidence: 89%
“…This is in line with the study of the development of media and teaching materials, among others [27] which has developed a learning model to improve job skills. At the same time, [28] also developed PISA-based student worksheets to improve students' problem skills. The development of teaching materials to improve students' hand-on ability was also carried out by [29] in his study, which stated that there is a relationship between the hand-on model against students who indulge in the law of energy conservation.…”
Section: Discussionmentioning
confidence: 99%
“…According to providing students with worksheets with PISAlike questions can improve their abilities to solve PISA problems (I. Kurniati et al, 2018). Contextual learning is accomplished not only by transferring material from the teacher to the students, but it can also help students gain proficiency in what they learn (Arini & Agustika, 2021;Suastika & Rahmawati, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the instruments used were test instruments and student response questionnaires. [13] The effectiveness of learning tools developed in terms: 1) completeness of student learning outcomes classically at least 85%; 2) achievement of learning objectives of at least 75%; 3) positive student response of at least 80%; and 4) the achievement of learning time did not exceed the normal learning time [16]. Improvement of students' mathematical representation ability was determined using the N-Gain formula from Hake [17] below.…”
Section: Methodsmentioning
confidence: 99%